Optimization of folic acid supplementation in the prevention of neural tube defects. (20th October 2017) - Cawley, Shona; McCartney, Daniel; Woodside, Jayne V; Sweeney, Mary Rose; McDonnell, Robert; Molloy, Anne M; Turner, Michael J
Abstract: Background: We examined the relationship between timing and duration of folic acid (FA) supplementation in achieving red blood cell (RBC) folate levels in early pregnancy which are optimal (>906 nmol/l) for the prevention of neural tube defects (NTDs). Methods: Clinical, FA supplementation and dietary folate details were computerized at the first antenatal visit. Maternal blood samples were analysed for RBC and serum folate. Results: Of the 502 women, 98.2% ( n = 493) reported taking FA. There was a positive correlation between duration of supplementation and both RBC folate ( r = 0.43, P < 0.001) and serum folate (rho = 0.29, P < 0.001). The optimal RBC folate level was achieved in 80.4% ( n = 46) of women who started FA 400 μg 4–8 weeks before their LMP compared with only 53.6% ( n = 153) in women who started 4–8 weeks after their LMP ( P < 0.001). Conclusions: This study provides, for the first time, information on both the timing and duration of FA that will achieve the optimum RBC folate levels associated with the prevention of NTDs. Women who are taking FA (400 μg) need to start before they conceive.